Does real exchange rate matter better than trade volumes in triggering labour productivity growth? Evidence from Ethiopia - Yekin Ahmed Ali (Cogent Economics & Finance, 2023)
The trade-growth relation remains one of the controversies unsettled to this date. We test this hypothesis taking Ethiopia as a case study. Ethiopia is a developing economy aspiring to achieve a middle-income level, yet its labour force remains one of the least productive. The study draws on data between 1950 and 2019 to explore the impacts of exports, imports, capital, and the real exchange rate on labour productivity growth of Ethiopia. The Dynamic Ordinary Least Square results reveal mixed results across the time periods. In the long- run, the real exchange rate and imports positively influence labour productivity growth while exports have a negative effect, and the short-run effects of capital and imports are negative but exports have a positive impact. The multivariate Granger-causality analysis shows that: in the long-run, the real exchange is exogenous, and capital, exports, and imports have two-way causal relationships with labour productivity. In the short- run, only capital Granger-causes labour productivity, and the reverse causation runs from labour productivity to exports and to the real exchange rate. The Variance Decomposition analysis demonstrates that the real exchange rate stands out as a macroeconomic policy variable stimulating not only productivity growth but also capital, exports, and imports. To improve the productivity of labour force, it is suggested that Ethiopia adopts a prudent trade policy to better reap the benefits of international trade, and to facilitate the transfer of foreign technology through importation. It also needs to diversify its export basket and switch exports from raw materials and semi-finished goods to high-value products.
Keywords: 330; Ethiopia; exports; imports; Labour productivity; real exchange rate